Woman with term presentation of acaridac twin pregnancy with three cesarean section scars: a case report - Leta Hinkosa Dinsa; Alemu Merga Hailu; Amenu Diriba Eticha (Journal of Medical Case Reports)
Abstract Background Twin reversed arterial perfusion sequence is the most severe and specific complication in monochorionic twin pregnancies, described by vascular anastomosis and partial or complete lack of cardiac development in one twin. Objective This report aims to present a unique discussion on cardiac twin pregnancy in an acardiac setting. In this acardiac twin pregnancy, one twin has no upper body part including the heart while the other twin (pump twin) has normal morphology. Acardiac twin pregnancy rarely reaches term, and the pump twin survives. Therefore, expectant management with close antenatal care follow-up can have good prognosis. Case summary We present a case of acardiac twin pregnancy. A 31-year-old G-IV P-III mother was referred to Wolegga University Teaching Referral Hospital for antenatal care service at gestational age of 24 weeks + 3 days from reliable last normal menstrual period. She is of Black African ethnicity, and on her first contact, twin intrauterine pregnancy with an acardiac twin was diagnosed. Then, expectant management was decided, and the pregnancy was closely monitored until term. At 38 weeks of gestation, an elective cesarean section was done. The acardiac twin died right away after the cord was clamped, while the pump twin is healthy and currently in follow-up. Conclusion Acardiac twin pregnancy rarely reaches term. To take prompt and appropriate measures, antenatal diagnosis of twin reversed arterial perfusion sequence is crucial.